2021
DOI: 10.1111/jopr.13388
|View full text |Cite
|
Sign up to set email alerts
|

Framework Fracture of Zirconia Supported Full Arch Implant Rehabilitation: A Retrospective Evaluation of Cantilever Length and Distal Cross‐Sectional Connection Area in 140 Patients Over an Up‐To‐7 Year Follow‐Up Period

Abstract: Purpose:To evaluate the relationship between different dimensional parameters in implant-supported monolithic zirconia fixed complete dental prostheses (IFCDPs) and the incidence of framework fracture in a large sample of cases in vivo. Materials and Methods:This retrospective observational study evaluated all patients rehabilitated with screw-retained zirconia IFCDPs between January 2013 and April 2019 at a private practice. The minimum follow-up period was 1 year after occlusal loading. Fractures were classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 34 publications
2
18
0
Order By: Relevance
“…Tirone et al reported on the CL or the thickness of the zirconia around the screw access opening (SAO) to the fracture of the structure [ 29 ], and their results were in line with those found in our study, because the SAO was the zone where there was a fracture in the zirconia structures. In order to overcome this problem, Alshiddi et al used a thickness increase of 0.5 mm around the distal SAO in order to reinforce it [ 9 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Tirone et al reported on the CL or the thickness of the zirconia around the screw access opening (SAO) to the fracture of the structure [ 29 ], and their results were in line with those found in our study, because the SAO was the zone where there was a fracture in the zirconia structures. In order to overcome this problem, Alshiddi et al used a thickness increase of 0.5 mm around the distal SAO in order to reinforce it [ 9 ].…”
Section: Discussionsupporting
confidence: 92%
“…With regard to CL, the results obtained in this study corroborate what is described by several authors [ 2 , 9 , 29 ]. Bearing in mind that the ideal cantilever length should not exceed 9 mm, in this study, structures with 6 mm and 10 mm cantilevers were tested in order to test their resistance to fracture.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, the difference in follow‐up periods between the present study and Diéguez‐Pereira and colleagues' 10 study may explain the variations in prevalence for complications. Previous studies on clinical success of complete‐arch implant‐supported zirconia prostheses were limited to 7 years of follow‐up 33,35–38 …”
Section: Discussionmentioning
confidence: 99%
“…Even though there are retrospective reports on implant‐supported zirconia prostheses, 3,8–10,28–38 the type of prosthetic complication that may be encountered depending on the prosthetic design is not clear, the design being a single‐unit, multi‐unit, or a complete‐arch fixed prosthesis. Clinicians can benefit from a long‐term retrospective study on clinical performance of implant‐supported zirconia prostheses with ti‐base abutments, focusing on the effect of prosthetic design.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation